T Cells Chemotaxis Migration Studies with a Multi-Channel Microfluidic Device - Yang Liu; Xiaoou Ren; Jiandong Wu; John A. Wilkins; Francis Lin (Micromachines, 2022)
Immune surveillance is dependent on lymphocyte migration and targeted recruitment. This can involve different modes of cell motility ranging from random walk to highly directional environment-guided migration driven by chemotaxis. This study protocol describes a flow-based microfluidic device to perform quantitative multiplex cell migration assays with the potential to investigate in real time the migratory response of T cells at the population or single-cell level. The device also allows for subsequent in situ fixation and direct fluorescence analysis of the cells in the microchannel.